Strengthening Public Health Surveillance Through Wastewater Testing : An Essential Investment for the COVID-19 Pandemic and Future Health Threats - Manuel, Doug; Amadei, Carlo Alberto; Campbell, Jonathon R.; Brault, Jean-Martin; Veillard, Jeremy (World Bank, Washington, DC, 2022)
Since early 2020, an outbreak of the coronavirus disease (COVID-19) caused by the 2019 novel coronavirus (SARS-CoV-2) has spread rapidly across the world. Latin America and the Caribbean remains an epicenter of the pandemic, with some of the world’s highest death rates. All countries in the region have been impacted, and more than 1.5 million people have died. With its relentless social and economic consequences, COVID-19 threatens to undo recent decades of progress on health outcomes in Latin America and the Caribbean and diverts attention from work on remaining health sector challenges. This report explores the value, potential, and challenges of wastewater testing for SARS-CoV-2 in Latin America and the Caribbean, including in areas without a sanitary sewerage system. Providing examples from across the world, the report also outlines what countries should consider in creating a national wastewater surveillance program as part of their broader efforts to control the impacts of COVID-19.